2007
DOI: 10.1007/s11747-007-0063-z
|View full text |Cite
|
Sign up to set email alerts
|

The service-dominant logic and a hierarchy of operant resources: developing masterful operant resources and implications for marketing strategy

Abstract: Marketing's evolution toward a new dominant logic requires the focus of marketing to be on the intangible, dynamic, operant resources that are at the heart of competitive advantage and performance. First, building on resourceadvantage theory's notion of basic resources and higher-order resources, this article proposes a hierarchy of basic, composite, and interconnected operant resources. Second, reviewing research on business strategy and marketing strategy, several resources that correspond to the proposed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
350
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(367 citation statements)
references
References 58 publications
14
350
0
3
Order By: Relevance
“…This is in line with Madhavaram and Hunt (2008), who suggested that dynamic capabilities can be viewed as operant resources, a stance also taken by Karpen et al (2015). Thus, the present study adopts the following definition of dynamic capabilities: dynamic capabilities are operant resources, working upon other operand and operant capabilities, that allow actors to systematically influence resource integration and institutions.…”
Section: Dynamic Capabilities As Micro-foundations For Institutionalsupporting
confidence: 69%
See 1 more Smart Citation
“…This is in line with Madhavaram and Hunt (2008), who suggested that dynamic capabilities can be viewed as operant resources, a stance also taken by Karpen et al (2015). Thus, the present study adopts the following definition of dynamic capabilities: dynamic capabilities are operant resources, working upon other operand and operant capabilities, that allow actors to systematically influence resource integration and institutions.…”
Section: Dynamic Capabilities As Micro-foundations For Institutionalsupporting
confidence: 69%
“…To date, the majority of dynamic capability researchers appear to agree that there are several types of capabilities, and that they exist at different orders, i.e., within a hierarchy of capabilities (Hine et al, 2014;Madhavaram and Hunt, 2008). While the original division was one between ordinary (non-dynamic) and dynamic capabilities (cf., Barreto, 2010), recently dynamic capabilities have been further divided into higher-and lower-order capabilities (Hine et al, 2014;Schilke, 2014).…”
Section: The Proposed Theoretical Frameworkmentioning
confidence: 99%
“…It provides an initial quantified perspective on the influence of what Madhavaram and Hunt (2008) term Binterconnected^op-erant resources that hold the potential to become Bmasterful^operant resources. The study brings together previously disparate perspectives from the technology management and marketing disciplines to create a new, holistic framework linking seller resources with buyer technology assimilation results that help capture S-D logic's co-creation of value element.…”
Section: Contributionsmentioning
confidence: 99%
“…To date, though, little quantitative analysis has been conducted to test the impact of these resources on value. Research has focused instead on classification systems (Madhavaram and Hunt 2008), consumer behavior (Arnould 2005), and conceptual integration into existing knowledge domains such as innovation theory (Michel et al 2008). Recent qualitative studies have highlighted the importance of sellers customizing offerings and communicating value in customer-specific terms (Tuli et al 2007;Ulaga and Reinartz 2011).…”
mentioning
confidence: 99%
“…Madhavaram and Hunt (2008) define resources as consisting of financial, physical, legal, human, organizational, informational, and relational resources. All these types of resources may be needed to adequately serve UMC customers, and their availability cannot be taken for granted in subsistence contexts.…”
Section: New Value Propositionmentioning
confidence: 99%